Detecting osteoporosis in elderly women with panoramic radiography technique - Barunawaty Yunus; Rezky Amalia (DiscoverSys Inc., 2016)
Osteoporosis is a systemic disease which characterized by a reduction in bone mass with deterioration microarchitecture of bone and degradation of bone tissue which can raise loss of bone. Osteoporosis is a problem related to the aging process. Osteoporosis process actually begin at the age 40-50 years. At this age, men and women will experience shrinkage process of bone mass. in women, this process faster after menopause and is more common in women than men. The technique can be used to detect osteoporosis by performing panoramic radiographic examination techniques. Panoramic radiography is a technique for generating photo of facial structures, including the maxillary bone, mandibular and other support structures. To detect the presence of osteoporosis in elderly women using Panoramic Radiography Techniques. The subjects of this study is image results of a panoramic radiography with vulnerable women aged 50-70> obtained from the Hospital Radiology section of Unhas, Mental Index measurement is then performed on image results of the panoramic radiographs. Overall regardless of age , the prevalence of osteoporosis reached 10 % per 100 population . ( P > 0.05). In detecting osteoporosis in elderly women, panoramic radiography can be applied. The index used is Mental Index, an index of panoramic radiography has been developed to detect osteoporosis.